2016
DOI: 10.3389/fphar.2016.00184
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor (HIF) as a Target for Novel Therapies in Rheumatoid Arthritis

Abstract: Hypoxia is an important micro-environmental characteristic of rheumatoid arthritis (RA). Hypoxia-inducible factors (HIF) are key transcriptional factors that are highly expressed in RA synovium to regulate the adaptive responses to this hypoxic milieu. Accumulating evidence supports hypoxia and HIFs in regulating a number of important pathophysiological characteristics of RA, including synovial inflammation, angiogenesis, and cartilage destruction. Experimental and clinical data have confirmed the upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 100 publications
2
68
0
Order By: Relevance
“…Given the role of hypoxia in RA and OA, targeting the stability of HIF-1α or HIF-2α and the hypoxic response might offer protection from multiple aspects of joint inflammation 113 . Similarly, modulators of glycolysis, such as PFKFB3 (REF.…”
Section: Immunometabolic Therapeutic Targetsmentioning
confidence: 99%
“…Given the role of hypoxia in RA and OA, targeting the stability of HIF-1α or HIF-2α and the hypoxic response might offer protection from multiple aspects of joint inflammation 113 . Similarly, modulators of glycolysis, such as PFKFB3 (REF.…”
Section: Immunometabolic Therapeutic Targetsmentioning
confidence: 99%
“…Fibroblast‐like synoviocytes, as the vital part of synovium, play a key role in RA pathogenesis by driving cartilage destruction and perpetuating inflammation . Although the molecular mechanisms are not fully understood, hypoxia and citrullination have been implicated in the pathogenesis of RA and have attracted much attention in the past decade . Citrullinated proteins can be found at extra‐articular sites, such as the lung, and the periodontal tissue, under the stimulating of smoking, and infections .…”
Section: Discussionmentioning
confidence: 99%
“…Early in the 1970s, significantly lower oxygen tensions in synovial fluids were observed in patients with RA in contrast to osteoarthritis (OA) patients . The high metabolic demand and rapid growth of synovial membrane in inflammatory synovial tissues led to the low oxygen state in RA joints . Studies have shown that hypoxia is involved in the pathogenesis and progression of RA by promoting inflammatory cytokines secretion, angiogenesis and cartilage destruction, and most likely through regulating HIF1α …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when stimulated by mitogens such as growth factors, MAPK expression increases significantly and have regulatory effects on multiple important pathophysiological processes including cellular growth, differentiation, stress, adaption to the environment, and the inflammatory response of tumor cells (18). MAPKs also play important roles in the biological growth process of tumor cells in that their expression normally correlates with the proliferation status of tumor cells, which is also the primary cause of metastasis of malignant tumor cells (1921). The present study showed that the expression of MAPK-p38 in the si-HIF-2α treated cells was lower than in the NC group, indicating that HIF-2α gene silencing can inhibit angiogenesis of osteosarcoma by lowering MAPK-p38 signaling, thus inhibiting the development and progression of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%